Double Investment Technique of Hollow Bulb Denture Obturator Fabrication in a Completely Edentulous Patient - Poonam Kulkarni; Rahul S. Kulkarni; Rupal J. Shah; Anup Vyas (Mashhad University of Medical Sciences, 2018)
Introduction: Prosthodontic management of palatal defects has been employed for many years. Palatal defects of any extent cause multiple problems in speech, mastication and aesthetics. Obturator prosthesis for an edentulous patient is more critical in terms of its movements as there is no mechanical retention available. Obturators and facial prostheses are important not only for rehabilitation and aesthetics, but also in patient resocialisation. Maxillary defects are created by surgical treatments of benign or malignant neoplasms and by trauma, in which case, denture is supported only by the underlying residual ridge and the defect. This clinical report describes the rehabilitation of a maxillary resected patient with a single piece hollow bulb denture obturator fabricated by double investment technique. Materials & Methods: In this double investment technique of hollow bulb denture obturator fabrication two same size transposable flasks were used for flasking and curing of the prosthesis. Results: Hollow bulb denture obturator was obtained by this double investment technique. Conclusion:  Decreased weight of prosthesis positively affects retention leading to improved physiologic function, and it also does not cause excessive atrophy in muscle balance.